Vegetação ciliar sob efeito de borda em matriz fragmentada na Amazônia Oriental - Volpato, Maristela (2020)
The objective of this work was to study the vegetation structure and composition from riparian Permanent Preservation Areas in a matrix fragmented by livestock in the eastern Amazon. The first chapter deals with the floristic description and the similarity between this vegetation and the reference area, in the second one the data were divided into segments to verify the effects of fragmentation along the vegetation strip and in the third one the influence of the soil variables on the species distribution in these areas. To achieve this information, the study was carried out on two stretches of fragments of riparian vegetation immersed in a pasture area and a stretch surrounded by native forest vegetation in the city of Juara, Mato Grosso. The adult vegetation, with diameter at breast height (DBH) ≥ 5 cm, measured at 1,30 m from the soil, was sampled in 10x30 m plots, measured from the watercourse, and subdivided into three 10x10 m plots, located at 0 to 10, 10 to 20 and 20 to 30 m from the watercourse. The regenerants were sampled in 2x2 m plots located at 10, 20 and 30 m from the watercourse in the left inner corner of the subplots. The floristic structure and composition of adult riparian vegetation in fragmented areas showed characteristics like to the reference area. The effects resulting from this event have been revealed, at first, with larger intensity in natural regeneration, to facilitate the colonization of herbaceous species that were not verified with such intensity in the reference area. In adult vegetation the effects were not so evident, but they should not be discarded, since woody plants have different mechanisms and may take a long time to manifest a response. We also verified that the vegetation has a high variation and that soil attributes such as humidity, organic matter, sand, clay and silt act in the ordering of the species.